Real-World Impact of Switching From Insulin Glargine (Lantus®) to Basaglar® and Potential Cost Saving in a Large Public Healthcare System in Saudi Arabia - AlRuthia, Yazed; Bahari, Ohud H.; Alghnam, Suliman; Alrumaih, Ali M.; Asiri, Hassan; Alshammari, Mohammed; Alhowimel, Mansour; Al-Abdulkarim, Hana A. (Frontiers in Public Health, 2022)
Background The advent of Basaglar®, which is a biosimilar insulin glargine formulation for Lantus® has brought hope that it will result in similar outcomes and lower costs. However, some health practitioners raised some concerns about the therapeutic equivalence of this new biosimilar. Therefore, we aimed to examine the clinical and financial impact of switching from Lantus® to Basaglar®. Methods This was a single–center retrospective chart review study of adult patients (e.g., ≥18 years) with diabetes mellitus (DM) who were treated with insulin glargine (Lantus®) for at least 12 months and then switched to Basaglar® for another 12 months. The potential cost savings for the years 2018 to 2021 and the cost avoidance for 2022 were estimated using different conversion ratios between the two insulin glargine products (Basaglar® and Lantus®) and acquisition prices. Results One–hundred patients with DM who were previously treated with Lantus® and switched to Basaglar® were retrospectively recruited. About two–thirds of the patients (68%) had type 2 DM, and the male and female patients were equally represented. The mean glycated hemoglobin (A1C) at baseline was 9, and the mean difference in the A1C levels before and after switching to Basaglar® was not significant (0.18, p-value = 0.503, 95% CI [−0.36–0.72]). Although the difference in the total daily insulin units between Lantus® and Basaglar® was not significant, the difference was leaning toward statistical significance despite the small sample size (−1.88, P-value = 0.25, 95% CI [−5.15–1.38]). Switching from Lantus® to Basaglar® could have led to significant cost savings that would range from approximately 1.77 to 23.7 million United States Dollars (USD) for the years 2018 to 2021 assuming an equal conversion ratio. However, those cost savings might not be realized if the switching to Basaglar® required higher daily insulin units, and the difference in the public tender acquisition price between Lantus® and Basaglar® is less than 15%. Conclusion Basaglar® and potentially other biosimilar insulin glargine products can lead to significant cost savings without compromising the quality of care. However, their acquisition prices should be discounted.